Unraveling a Secret : Vietnam's Outstanding Performance on the PISA Test - Parandekar, Suhas D. (World Bank, Washington, DC, 2016)
This paper seeks to find an empirical explanation of Vietnam's outstanding performance on the Programme for International Student Assessment (PISA) in 2012. Only a few developing countries participate in the assessment. Those who do, with the unique exception of Vietnam, are typically clustered at the lower end of the range of the Programme for International student Assessment scores. The paper compares Vietnam's performance with that of a set of seven developing countries from the 2012 assessment's data set, using a cut-off per capita GDP (in 2010 purchasing power parity dollars) of $10,000. The seven developing countries' average performance lags Vietnam's by more than 100 points. The "Vietnam effect" is difficult to unscramble, but the paper is able to explain about half of the gap between Vietnam and the seven countries. The analysis reveals that Vietnamese students may be approaching their studies with higher diligence and discipline, their parents may have higher expectations, and the parents may be following up with teachers regarding those expectations. The teachers themselves may be working in a more disciplined environment, with tabs being kept on their own performance as teachers. Vietnam may also be benefiting from investments in pre-school education and in school infrastructure that are disproportionately higher when compared with Vietnam's per capita income level.